Figure 32 from: Eberhardt U, Beker HJ, Borgen T, Knudsen H, Schütz N, Elborne SA (2021) A survey of Hebeloma (Hymenogastraceae) in Greenland. MycoKeys 79: 17-118. https://doi.org/10.3897/mycokeys.79.63363 - Eberhardt, Ursula; Beker, Henry J.; Borgen, Torbjørn; Knudsen, Henning; Schütz, Nicole; Elborne, Steen A. (Zenodo, 2021)
Figure 32 Hebeloma leucosarxA JV06-757 (from Denmark), photo J. Vesterholt, reproduced by kind permission from Beker et al. (2016)B distribution of cited collections C spores ×1600 and D cheilocystidia ×1000 of TB81.211 in Melzer's reagent. Scale bars: 5 µm; microphotographs H.K.J. Beker.